Stulecie Kodeksu cywilnego szwajcarskiego - Sójka-Zielińska, Katarzyna (Czasopismo Prawno-Historyczne, 2018)
The Swiss Civil Code (Schweizerisches Zivilgesetzbuch – ZGB) came into being on 1 January 1912 culminating the series of so called great civil codifications of continental Europe. The vast experience in the codification work within the Roman legal culture allowed the editors of the ZGB, and its author, Eugen Huber in particular, to create a truly original work that perfectly combined long legal traditions of individual Swiss cantons with the requirements of contemporary expectations, the ideas of individualism with those of social solidarity, the liberal slogans with the policy of interventionism, and the letter of law with the principles of equity and the canons of ethics. The staring point for the Swiss Civil Code was a draft authored by W. Munziger, which referred to the Zurich Code Civil, the German commercial code, the Austrian ABGB of 1861 and the Dresdener law of obligations of 1866. Another important stage was the initiative of the Swiss Juristenverein which in 1884 proposed a comparative study of all cantonal private law systems. The results of that study were to serve as a basis for the future nationwide unification of the legal system. Between 1893 and 1898 Eugen Huber developed three preliminary drafts, covering family law, succession law and rights in property. In 1900 they were published as a government project and put forward for a public discussion carried out by a 31-member expert group, with wide participation of individual citizens and interest groups. Eventually, on 10 December, the project was unanimously adopted as Schweizerisches Zivilgesetzbuch, Codice civile svizzero (ZGB) to come into force and be binding as of 1 January 1912. Among the many states drat drew on the Swiss Civil Code when drafting their own codes were Lichtenstein, Austria, Hungary, Greece, Italy and Turkey. In the latter, the ZGB was adopted as part of the reforms under Kamal Atatürk. The Swiss codification was highly valued by the civil lawyers in the Second Polish Republic.